2012
DOI: 10.2478/s13380-012-0024-y
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic epidemiology in psychiatry: A translational neuroscience perspective

Abstract: Introductiondifferential epigenetic profiles) for epigenetic involvement in the most prevalent and severe psychiatric illnesses. We will end the article by discussing current research challenges in epigenetic epidemiology and neuroscience, and we propose that more studies combining epidemiological and neuroscience approaches in studying epigenetics are needed to improve our understanding of the role of the epigenetic machinery in the etiologies of psychiatric disorders. Besides robust changes in reprogramming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 229 publications
0
2
0
Order By: Relevance
“…Animal data suggest that these neurochemical and behavioral changes in adults may have their origins in perinatal exposure, e.g. to 5-HT precursor 5-hydroxytriptophan, 5-HTP, or MAO inhibitors (Blažević and Hranilović, 2013), as well as other pre- and postnatal factors, most likely via epigenetic mechanisms (Pishva et al, 2012). Such changes have also been described as a part of the clinical picture in very early stages of AD (Cummings, 1992; Mychack et al, 2001; Michelsen, 2008).…”
Section: Monoaminergic Systems In Admentioning
confidence: 99%
“…Animal data suggest that these neurochemical and behavioral changes in adults may have their origins in perinatal exposure, e.g. to 5-HT precursor 5-hydroxytriptophan, 5-HTP, or MAO inhibitors (Blažević and Hranilović, 2013), as well as other pre- and postnatal factors, most likely via epigenetic mechanisms (Pishva et al, 2012). Such changes have also been described as a part of the clinical picture in very early stages of AD (Cummings, 1992; Mychack et al, 2001; Michelsen, 2008).…”
Section: Monoaminergic Systems In Admentioning
confidence: 99%
“…A growing body of evidence from human and animal studies suggests that the ability to regulate emotions is influenced by genetic liability, environmental exposures over the life course, as well as personality traits and coping styles. While the biological basis of emotion regulation and inter-individual variability in the response to stress remains incompletely understood, a flux of recent investigations has shown that epigenetic regulation of gene expression can mediate experience-dependent plasticity (structural and functional changes in the brain in response to environmental exposures and experiences) [3] and may thus play a crucial role in regulating the impact of environmental exposures on psychological and biological functioning of the individual [4] . DNA methylation, that is, the chemical addition of methyl groups to nucleotides, is a key epigenetic mechanism influencing gene expression.…”
Section: Introductionmentioning
confidence: 99%